1999
DOI: 10.1080/026782999204561
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation study of a nematogenic lattice model based on an elastic energy mapping of the pair potential

Abstract: Director con® gurations in a nematic liquid crystal can be determined by minimizing its total elastic free energy, for given elastic constants and speci® c boundary conditions. In some cases, these con® gurations have been obtained by numerical procedures where the elastic free energy density plays the same role as the overall potential energy in a standard Metropolis Monte Carlo simulation. The interaction energies or potentials used in these studies are short ranged but, in general, not pairwise additive, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 49 publications
1
32
0
1
Order By: Relevance
“…3(b) match identically with previous investigations based on long-wavelength director fluctuations [42]. [44] splits the elastic constants of bend, twist and splay deformations (diagrams at left). The elastic ratios of these coefficients (determined by BFS) for a model representing paraazoxyanisole (PAA) are given in the plot at right, with the expected ratios recovered as temperature is quenched toward zero [30].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…3(b) match identically with previous investigations based on long-wavelength director fluctuations [42]. [44] splits the elastic constants of bend, twist and splay deformations (diagrams at left). The elastic ratios of these coefficients (determined by BFS) for a model representing paraazoxyanisole (PAA) are given in the plot at right, with the expected ratios recovered as temperature is quenched toward zero [30].…”
supporting
confidence: 87%
“…4 we show that our method also captures the elastic ratios associated with generalized LL models; the model considered here was derived to describe para-azoxyanisole (PAA) in the limit of zero temperature [30,44]. Our simulations clearly obtain the correct elastic anisotropy at low T * , with logarithmic growth in both ratios approaching the isotropic-nematic transition.…”
mentioning
confidence: 66%
“…It is the molecular anisotropy which is held responsible for the longrange orientational order of thermotropic liquid crystals, be they formed from rod-or disc-like molecules. However, for many years it was not clear what were the roles played by anisotropic repulsive and attractive forces in determining liquid crystal behaviour [3]. Thus, the success of MaiereSaupe theory of nematics seemed to suggest that it is the attractive forces which are dominant, but less successful hard particle theories have also contributed to our understanding of liquid crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the study of hard ellipsoids which revealed that for both rods and discs the system will exhibit nematic behaviour provided the shape anisotropy is sufficiently large. The inability of hard ellipsoids to form smectic or columnar phases is of special importance, but it should be noted that systems of other hard objects have been found to form such translationally ordered phases [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years there has been increasing interest in stable phases mediating the transition between different liquid crystalline phases (Rananavare et al, 1994;Rao et al, 1996;Srinivasulu et al, 1997;Potukuchi et al, 1998;Kumar et al, 2000). Further, computer simulation is finding an increasingly influential role for understanding liquid-crystal phases (Wilson and Allen, 1991;Bates and Luckhurst, 1997); Luckhurst and Romano, 1999;Blatch and Luckhurst, 2000;Sarman, 2000). However, it is essential to study simple models in some depth in order to understand the forces responsible for mesophase formation.…”
Section: Introductionmentioning
confidence: 99%